Control of Sitophilus oryzae (Coleoptera: Curculionidae) in bags of wheat using solar radiation. (March 2022) - Fawki, S.; Fields, P.G.; Jian, F.; Yousery, A.
Abstract: Solar heating disinfestation is a promising technique for low-income farmers in developing countries. Solar disinfestation of Sitophilus oryzae in wheat was investigated using clear and black polyethylene plastic bags and woven bags. Different amounts of wheat (16, 21, and 25 kg) with 12.2% moisture content (wet basis) were tested under two field conditions: 1) wheat bags were kept at the field with no stacking or mixing; 2) wheat bags were mixed at the end of the day and stacked during the night. The experiment was conducted in Canada and Egypt. Degree-minutes and time above 40 °C for each treatment were also calculated. Wheat inside clear polyethylene bags heated up to a temperature range of 40–55 °C, which is considered lethal to many stored-grain insects, including S. oryzae . Mortality of adult S. oryzae was 67.6 ± 30% for clear plastic bags and 4.3 ± 0.8% for woven plastic bags. In general, degree-minutes and time above 40 °C inside 16 kg of wheat bags were significantly higher than bags with 21 or 25 kg of wheat. Highlights: Solar disinfestation of S. oryzae in wheat in different sized bags was tested. Different wheat amounts of wheat; 16, 21, and 25 kg were tested. Upper layers of wheat in clear bags reached 50 ± 5 °C. Bottom layers of wheat in clear bags reached 40–45 °C. Adult moralities were 68% in clear-plastic bags and 4% in woven-plastic bags.